Question
1- iota
2 .-1 - iota
3.√3+iota
Answers
Answered by
1
✌♥✌hey mate here is your answer ✌♥✌
⛄1) iota = √-1
-iota=-√-1⛄
♥2) -1-iota= -1-√-1
=-(1+√-1)♥
✌3)√3+iota = √3+√-1✌
✌♥✌ hope it will help you ✌♥✌
⛄✌✌mark me brainliest ✌✌⛄
✌^_^✌HAPPY NEW YEAR 2K19✌^_^✌
⛄1) iota = √-1
-iota=-√-1⛄
♥2) -1-iota= -1-√-1
=-(1+√-1)♥
✌3)√3+iota = √3+√-1✌
✌♥✌ hope it will help you ✌♥✌
⛄✌✌mark me brainliest ✌✌⛄
✌^_^✌HAPPY NEW YEAR 2K19✌^_^✌
Answered by
3
ĀNSWĒR ⏬
1.) √2 (-π/4+sin -π/4 iota )
2.) √2(cos(-3π/4)+iota sin(-3 π/4)
3.) 2(cosπ/6+iota sinπ/6)
for full solution check out the attachment.
THANKS ❤
#Nishu HarYanvi ♥
1.) √2 (-π/4+sin -π/4 iota )
2.) √2(cos(-3π/4)+iota sin(-3 π/4)
3.) 2(cosπ/6+iota sinπ/6)
for full solution check out the attachment.
THANKS ❤
#Nishu HarYanvi ♥
Attachments:
![](https://hi-static.z-dn.net/files/da0/360a39ed4f16a07e7cfdaa6f1f4464f3.jpg)
![](https://hi-static.z-dn.net/files/daa/c60a82a2b743bafaae22a38bdf5af69a.jpg)
![](https://hi-static.z-dn.net/files/d3c/dbb32cdcd46ecc7654f705a5f29e9f3d.jpg)
Similar questions